2018
DOI: 10.4314/ajcem.v19i4.6
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic bacteriuria in an apparently healthy population and its relation to hypertension

Abstract: Background Hypertension is a major health problem in sub-Sahara Africa. Several studies have suggested a role of asymptomatic bacteriuria (ASB) in the aetiology of hypertension, but there is a dearth of information on this association in Africa where the burden of hypertension is high. We investigated the prevalence of asymptomatic bacteriuria, its association with hypertension and determined the antibiotic resistance patterns of implicated bacterial isolates in an urban community of Ile-Ife. Methods One hundr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…The high frequency of E. coli isolation indicates its continued significance in the aetiology of urinary tract infections, gastrointestinal infections and bloodstream infections, which accounted for more than 85% of suspected clinical infections in this study. Majority of the Gram-negative isolates were from urine samples, which formed the highest number of clinical samples in this study, supporting the fact that urine is the most common routine samples received at the clinical microbiology laboratory, even as E. coli is the most common bacteria aetiology of uncomplicated urinary tract infection [17]. Antimicrobial resistance in the health care setting, although not a new problem, is worrisome as it affects the efficacy of antimicrobial agents.…”
Section: Discussionsupporting
confidence: 66%
“…The high frequency of E. coli isolation indicates its continued significance in the aetiology of urinary tract infections, gastrointestinal infections and bloodstream infections, which accounted for more than 85% of suspected clinical infections in this study. Majority of the Gram-negative isolates were from urine samples, which formed the highest number of clinical samples in this study, supporting the fact that urine is the most common routine samples received at the clinical microbiology laboratory, even as E. coli is the most common bacteria aetiology of uncomplicated urinary tract infection [17]. Antimicrobial resistance in the health care setting, although not a new problem, is worrisome as it affects the efficacy of antimicrobial agents.…”
Section: Discussionsupporting
confidence: 66%
“…Isolation of S. aureus and S epidermidis is not limited to our study. Previous studies in the study environment and across the globe similarly reported them as frequently isolated uropathogens 14,30,34 . Isolation of these bacteria may be because they are mostly normal skin flora and can be accidentally introduced to the urethra during sexual intercourse 37 .…”
Section: Discussionmentioning
confidence: 80%
“…Globally, E. coli is the commonest uropathogens implicated in ASB 32 , 33 . Previous studies in Nigeria have also reported it as the commonest pathogen implicated in ASB 28 , 34 . Consequently, its dominance is in tandem with the previous reports.…”
Section: Discussionmentioning
confidence: 90%